Immobilisation and Epidural Anaesthesia in a Eurasian Lynx (Lynx lynx) Undergoing Pelvic Limb Orthopaedic Surgery - Sonia Campos; Pierre Picavet; Olivier Bertrand; Charlotte Sandersen; Alexandru Tutunaru (Case Reports in Veterinary Medicine)
Immobilisation and anaesthesia of wild felids may be complex and potentially dangerous events, making it difficult to implement more advanced anaesthetic techniques such as neuraxial anaesthesia. A Eurasian lynx was referred for femur fracture repair after it was seen with lameness of the left pelvic limb sustained in its natural environment. The animal was remotely darted using a combination of ketamine (5 mg/kg) and xylazine (5 mg/kg) intramuscularly. Once immobilised, the lynx was transported to the veterinary hospital in a restraining cage. After induction and endotracheal intubation, pelvic limb radiographs confirmed a closed, comminuted fracture of the left femur that required open reduction and internal stabilisation. A sacrococcygeal epidural was performed before surgery using lidocaine (2 mg/kg) and morphine (0.1 mg/kg) to complement the ketamine–xylazine–isoflurane anaesthesia, which allows a low-end-tidal isoflurane concentration. Clinical signs were continuously monitored and remained stable during the entire procedure, with the exception of a temperature that decreased to 35.8°C. No intraoperative analgesic rescues were necessary. Recovery was smooth and uneventful. The lynx showed no signs of motor weakness after surgery or other side effects related to the anaesthetic procedure. The successful management of this surgical case suggests that the described anaesthetic protocol could be recommended in orthopaedic procedures of the pelvic limbs in wild Felidae.